Pengaruh Daftar Menu Sistem Barcode dan Pembayaran Qris Terhadap Kepuasan Pelanggan Coffee Toffee Airlangga - Vania Winda Ramadhani; Arman Arman (Journal of Management and Bussines (JOMB), 2023)
This research was conducted to determine the effect of the barcode system menu and QRIS payments on consumer satisfaction from Airlangga Toffee Coffee consumers. Data analysis techniques use statistical analysis such as the t test, F test, and linear regression to determine the effect of the barcode system menu list and QRIS payments on customer satisfaction. The data collection technique uses a questionnaire. The research results show that the results of the barcode system menu and QRIS payments have an influence on consumer satisfaction. In conclusion, Coffee Toffee Airlangga has a Barcode System Menu List which contributes to customer satisfaction. Keywords: Consumer Satisfaction, Product Quality, Consumer Loyalty